Porcine Circovirus Type 2 Activates CaMMKβ to Initiate Autophagy in PK-15 Cells by Increasing Cytosolic Calcium - Yuanxing Gu; Baozhu Qi; Yingshan Zhou; Xiaowu Jiang; Xian Zhang; Xiaoliang Li; Weihuan Fang (Viruses, 2016)
Porcine circovirus type 2 (PCV2) induces autophagy via the 5′ adenosine monophosphate-activated protein kinase (AMPK)/extracellular signal-regulated kinase (ERK)/tuberous sclerosis complex 2 (TSC2)/mammalian target of rapamycin (mTOR) pathway in pig kidney PK-15 cells. However, the underlying mechanisms of AMPK activation in autophagy induction remain unknown. With specific inhibitors and RNA interference (RNAi), we show that PCV2 infection upregulated calcium/calmodulin-dependent protein kinase kinase-beta (CaMKKβ) by increasing cytosolic Ca2+ via inositol 1,4,5-trisphosphate receptor (IP3R). Elevation of cytosolic calcium ion (Ca2+) did not seem to involve inositol 1,4,5-trisphosphate (IP3) release from phosphatidylinositol 4,5-bisphosphate (PIP2) by phosphoinositide phospholipase C-gamma (PLC-γ). CaMKKβ then activated both AMPK and calcium/calmodulin-dependent protein kinase I (CaMKI). PCV2 employed CaMKI and Trp-Asp (WD) repeat domain phosphoinositide-interacting protein 1 (WIPI1) as another pathway additional to AMPK signaling in autophagy initiation. Our findings could help better understanding of the signaling pathways of autophagy induction as part of PCV2 pathogenesis. Further research is warranted to study if PCV2 interacts directly with IP3R or indirectly with the molecules that antagonize IP3R activity responsible for increased cytosolic Ca2+ both in PK-15 cells and PCV2-targeted primary cells from pigs.